Blending Online and In-Person Seminars to Strengthen Clinical Placement Learning in Physiotherapy Education - Wojniusz S; Langaas AG; Røe Y (Advances in Medical Education and Practice)
Slawomir Wojniusz, Anne Gudrun Langaas, Yngve Røe Department of Rehabilitation Science and Health Technology, Oslo Metropolitan University, Oslo, NorwayCorrespondence: Slawomir Wojniusz, Oslo Metropolitan University, Postboks 4, St. Olavs plass, Oslo, 0130, Norway, Email slawomir@oslomet.noIntroduction: Digital technology continues to reshape health professions education, yet little is known about the relative effectiveness of synchronous online versus in-person collaborative learning in strengthening clinical placement experiences for physiotherapy students. This study examined physiotherapy students’ expectations, perceptions, and preferences regarding online and in-person small-group seminars.Methods: A quasi-randomized crossover design was used in two course iterations (I-1, I-2) involving 106 final-semester physiotherapy students. Participants were split into groups of 5– 6 to engage in ten seminars discussing complex clinical cases drawn from their prior placements, with half of the groups starting online and later switching to in-person, and vice versa. A third iteration (I-3; n=77) alternated between online and in-person sessions following two initial in-person seminars. Data were gathered through anonymous electronic surveys containing Likert-scale ratings and open-text responses. Quantitative data were analyzed with t-tests and chi-square tests; qualitative comments underwent thematic analysis.Results: Mid-course evaluations revealed no significant differences in perceived effectiveness when students had experienced only one format. By the course’s end, however most students ultimately favored in-person seminars for richer social interaction (I-2: 80%; I-1: 38%; I-3: 54%), although they consistently recognized online sessions as time-efficient and flexible. Notably, students’ initial expectations (I-1 and I-2) strongly mirrored their final evaluations. Qualitative feedback highlighted that in-person seminars provided higher-quality social interactions, while online seminars offered greater efficiency and flexibility. Most students indicated a preference for a blended format in future courses.Conclusion: By blending in-person and online sessions, collaborative seminars can give physiotherapy students the best of both worlds for their clinical placement learning. Meeting in-person fosters richer discussions and deeper social connections, while online sessions offer efficiency, flexibility and help students develop essential digital competence. Together, these formats create a more adaptable, forward-looking learning environment that aligns with the evolving demands of professional practice.Keywords: collaborative learning, online learning, health professions education, group seminars, physiotherapy education, clinical placement